Numerical analysis of flow heat transfer characteristics and optimization of double-layered microchannel heat sinks with different structures - Bo Cai; Pan Hu; Yifan Li; Bingzhi Chen; Haoyang Cai (Case Studies in Thermal Engineering)
This paper proposes a novel double-layered microchannel heat sink (TMC-ORTC), specifically, the upper layer consisted of a truncated rectangular microchannel, while the lower layer features a microchannel that combines trapezoidal cavity with oval rib. The flow and heat transfer characteristics of 8 distinct configurations of double-layer microchannel heat sinks (DL-MCHSs) are investigated through numerical simulations at Reynolds numbers (Re) ranging from 150 to 950. Various performance parameters, including pressure drop, friction coefficient, thermal resistance, average Nusselt number (Nu), temperature uniformity, entropy production and heat transfer enhancement factor, are analyzed respectively. The structural parameters of TMC-ORTC are optimized by multi-objective genetic algorithm with thermal resistance, pumping power and temperature uniformity as optimization objectives. The results indicate that the combination of cavity and rib microchannel leverages the benefits of ribs to enhance fluid disturbance and heat transfer, while cavities serve to increase the flow area within the microchannel and reduce pressure drop. Among all the DL-MCHSs studied in this paper, compared with the single arrangement of cavity or rib structure within the microchannel, the combination of cavity and rib structure results in a more pronounced enhancement of the flow and heat transfer performance of the DL-MCHS. The TMC-ORTC outperforms other microchannel heat sinks (MCHSs) in comprehensive performance. When Re = 895.69, compared with the traditional double-layered rectangular microchannel heat sinks (MC-MC), the average Nusselt number of TMC-ORTC has increased by 121.67 %, the temperature uniformity is increased by 81.7 %, the maximum heat transfer enhancement factor is 1.899, the minimum value of augmentation entropy generation number (Ns,a) is 0.89. The optimization results show that when the width of oval rib (Wr) is 0.056 mm and the truncated length of the upper microchannel (Lx) is 1.494 mm, the comprehensive performance of TMC-ORTC is the best.